2003
DOI: 10.1127/0003-9136/2003/0157-0535
|View full text |Cite
|
Sign up to set email alerts
|

Shelter use of the Red-Swamp Crayfish (Procambarus clarkii) in dry-season stream pools

Abstract: Abstract:Patterns of shelter use of the red-swamp crayfish, Procambarus clarkii, were studied in a temporary stream of the south of the Iberian Peninsula during the summer of 1999. By shelters, we mean both excavated burrows and natural refuges, such as crevices under rocks, boulders, and stones. Both crayfish shelter use and faithfulness, and the relationship between the use of shelters and some abiotic parameters of the habitat were analysed. Five main issues were raised. (1) Crayfish did not hide exclusivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 21 publications
0
16
1
Order By: Relevance
“…Procambarus clarkii typically reaches sexual maturity at -40 mm CL and mates during summer, a period when reproductive adults, especially females, often seek shelter in burrows (Gherardi et al 1999, Ilheu et al 2003, Penn 1943. In Pine Lake, the reproductive cycle of P. clarkii is similar to the pattern reported for many populations of the species (Mueller 2007a).…”
Section: Discussionmentioning
confidence: 80%
“…Procambarus clarkii typically reaches sexual maturity at -40 mm CL and mates during summer, a period when reproductive adults, especially females, often seek shelter in burrows (Gherardi et al 1999, Ilheu et al 2003, Penn 1943. In Pine Lake, the reproductive cycle of P. clarkii is similar to the pattern reported for many populations of the species (Mueller 2007a).…”
Section: Discussionmentioning
confidence: 80%
“…Nevertheless, our analyses showed that, at the early stages of the invasion, wetland features can be extremely important for crayfish distribution: P. clarkii was strongly associated to large and permanent wetlands. Wetland hydroperiod is known to be a limiting factor for the presence of this species: P. clarkii can also be found in temporary wetlands, but in such habitats it needs shelter, like boulders, wood debris, crevices or a silt substrate to make burrows and retain the humidity, allowing their survival (Correia and Ferreira 1995;Ilhéu et al 2003;Cruz and Rebelo 2007). Furthermore, wetlands should have a hydroperiod longer than 4 months for the persistence of P. clarkii (Gutiérrez Yurrita and Montes 1999).…”
Section: Invasion Processesmentioning
confidence: 98%
“…However, our study focused for the first time on the relationship between used and available microhabitats and it supported the hypothesis that crayfish occupancy of a given substrate is independent of its availability (crayfish avoid microhabitats without boulders) but is related to crayfish size (larger crayfish are associated with larger substrates). Indeed, an appropriate substrate may provide shelters to protect crayfish from predation (Ilhéu et al 2003) and to prevent their drift (M. Ilhéu, unpublished data).…”
Section: Discussionmentioning
confidence: 99%